Effect of Wide-Spectrum Pulsed Magnetic Field on Solidification Structure of Pure Al at Constant Flow Velocity - Yawei Sun; Bohuai Yao; Zhen Zhao; Yongyong Gong (Metals, 2023)
The electromagnetic force generated by a pulsed magnetic field within a metal melt leads to changes in the internal temperature and flow fields of the molten metal, thus improving the solidification of the metal structure. Using the combination of a solidification test, experimental simulation and theoretical analysis, this study simulated the distribution of both electromagnetic force and the flow field in a metal melt under wide-spectrum pulse conditions, and studied the influence of a wide-spectrum pulsed magnetic field on the solidification structure of pure aluminium with a constant flow velocity. The results of this study show that the structural refinement of the solidification of pure aluminium can be different, in spite of equal flow velocity. Furthermore, this study shows that an applied time-averaged electromagnetic force causes crystal nuclei to pass through the solid–liquid interface boundary layer and promotes the growth of crystal grains. These grains flowed with the melt flow field to achieve both refinement and homogenization of the solidified structure.